Camera EDSA obscura - Manzanilla, John Paul S. (2012)
Twenty years after the EDSA uprising, 20 independent filmmakers created 20 films showing different images of the country. Ending the project with the film Mistulang Kamera Obskura, the omnibus film project self-critically staged its representation of the social and the political. The camera obscura has a long and fraught history as a metaphor of ideology, most prominently broached by Marx in his discussion of being, consciousness, and ideology. Reading the moving images as concretizations of ideas, it seeks to limit those ideas as constitutive of the various ideologies of the EDSA uprising which the filmmakers represent in the process of "depicting truthful images of the nation."
Keywords: Motion pictures -- Social aspects; Social problems in motion pictures; Politics in motion pictures